Attitude and Motivators of Community Dwelling Older Adults Toward Using Mobile Health Technology (Cuestiones de Fisioterapia, 2024)
Background: Mobile health technology presents opportunities for health management in older adults. Although it can enhance monitoring and communication with healthcare providers, there are barriers that may impede its adoption. Aim of the study: Evaluate attitude and motivators of community dwelling older adults toward using mobile health technology. Subjects and Methods: Research design: Descriptive design. Setting: The study was conducted at Fadadna village, Fakous city, Sharkia governorate, Egypt, which was randomly selected by using the multistage cluster sampling technique. Subjects: The study subjects were 300 rural older adults, a purposive sample was used